Behaviour and cross-contamination of pathogenic bacteria in household kitchens : - Kusumaningrum, Harsi Dewantari (Wageningen Universiteit, 2003)
Illness resulting from consumption of contaminated food is a continuous serious public health problem in the world. A proportion of this foodborne disease is attributable to improper preparation practices in the home, including cross-contamination.